Determination of receiver code bias variations with a modified geometry-free GNSS model. Issue 1 (2nd January 2022) - Ke, Cheng; Sheng, Chuanzhen; Wang, Shengli
ABSTRACT: Receiver code biases (RCBs) have long been identified as time-constant. However, RCBs can exhibit remarkable intraday variability, which affects GNSS-based ionospheric retrieval and timing applications with different combinations. Previous studies remain on characterizing the variation of geometry-free linear combinations. In this contribution, we propose a modified geometry-free (MGF) GNSS model to extract the receiver code bias variations (RCBVs). We collect 153 stations to test the MGF model and characterize the estimated RCBVs. The results show that RCBVs bear a strong linear correlation with intraday temperature, which is receiver and constellation dependent. Many stations exhibit significant RCBV, even 10% of stations, of which RCBV exceeds 5 ns.